Nematode communities along a bathymetric transect in the deep eastern Fram Strait (Arctic Ocean): interrelations between diversity, function and environment - Jannik Schnier; Christiane Hasemann; Vadim Mokievsky; Pedro Martínez Arbizu; Thomas Soltwedel (Frontiers in Marine Science, 2023)
As an expansion of a time-series study on meiobenthos in the Arctic deep sea, the diversity of free-living nematode communities along nine stations along a bathymetric transect was investigated morphologically in taxonomic and functional regards (feeding-type composition, life-history traits, tail-shape composition) and compared with previous studies of the same transect to investigate possible changes in the nematode community composition. Special emphasis was given on the analysis of sedimentary environmental parameters, which are used as proxies for food availability and sediment porosity. Multivariate statistics performed on nematode abundance data revealed a bathymetric zonation into four bathymetric zones: upper bathyal (1300 – 2000 m), lower bathyal (2500 - 3500 m), abyssal (5100 – 5600 m) and an additional ‘outgroup’ consisting of two stations with low nematode densities. Nematode densities generally decreased with increasing depth. Taxonomic diversity (EG(50), H’(log2), J’) decreased in a unimodal pattern peaking in the lower bathyal zone. A distance-based linear model revealed that 44% of the total variation in nematode abundances could be explained by the measured environmental parameters. Microbial feeders are the dominant feeding type along the transect with increasing dominance in the abyssal zone. The maturity index, a measure of environmental disturbance, decreased with depth, indicating a more colonizer-dominated community in the abyssal zone. Nematodes with long conico-cylindrical tails also become more dominant in the abyssal zone. A previous study of the same transect conducted in 2005 found a similar bathymetric zonation, but with a strikingly different dominant feeding type, i.e. epistrate feeders. Between the 2005 study and the year 2010 we conducted our study, the composition of the plankton community in the Fram Strait changed significantly due to a warm water anomaly in the region. We argue that through bentho-pelagic coupling, effects of this warm water anomaly on plankton communities could be a reason for the drastic change in dominant nematode feeding types.